Three Rickettsioses, Darnley Island, Australia - Nathan B. Unsworth; John Stenos; Antony G. Faa; Stephen R. Graves (Emerging Infectious Diseases, 2007)
We report 3 rickettsioses on Darnley Island, Australia, in the Torres Strait. In addition to previously described cases of Flinders Island spotted fever (Rickettsia honei strain “marmionii”), we describe 1 case of Queensland tick typhus (R. australis) and 2 cases of scrub typhus caused by a unique strain (Orientia tsutsugamushi).